723 Neuroendoscopy versus Craniotomy in Basal Ganglia Haemorrhage: A Systematic Review and Meta-Analysis. (12th October 2021) - Tan, T K; Merola, J; Zaben, M; Gray, W; Leach, P
Abstract: Aim: Basal ganglia haemorrhage (BGH) is the most common type of intracerebral bleed with high morbidity and mortality rate. The efficacy between craniotomy and endoscopic approach in BGH is still debatable and advancement in minimally invasive technique has made endoscopic approach the preferred option. The aim of this systematic review and meta-analysis was to evaluate the outcomes of craniotomy and endoscopic approach in BGH. Method: Databases of PubMed, EMBASE, MEDLINE and CENTRAL were systematically searched from its inception until December 2020. All randomized clinical trials and observational studies comparing craniotomy versus endoscopic approach in BGH were included. Results: Twelve studies enrolling 1297 patients (craniotomy:675, endoscopy:632) were included for qualitative and quantitative analysis. Endoscopic approach was associated with significantly lower postoperative mortality (OR:0.35, P < 0.00001), higher haematoma evacuation rate (MD:4.95, P = 0.0002), shorter operative time (MD:-117.03, P < 0.00001), lesser intraoperative blood loss (MD:-328.47, P < 0.00001), higher postoperative Glasgow Coma Scale (GCS) (MD:1.14, P = 0.01), higher postoperative Glasgow Outcome Scale (GOS) (MD:0.44, P = 0.05), shorter length of hospital stay (MD:-2.90, P < 0.00001), lower complication rate (OR:0.30, P = 0.0004), lower infection rate (OR:0.29, P < 0.00001) and lower modified Rankin Scale (mRS) (MD:-0.57, P = 0.004) compared to craniotomy. No significant difference was detected in reoperation, intracranial infection, re-bleeding. Conclusions: The best available evidence suggest that endoscopic approach has better outcomes in mortality rate, operative time, haematoma evacuation rate, intraoperative blood loss, length of hospital stay, mRS, postoperative GCS and GOS compared with craniotomy in the management of BGH. However, there is a need for high quality randomised controlled trials with large sample size for definite conclusions.